Early Child Development Questionnaire for 0-2 Years (ECD-Questionnaire) - Hendriati Agustiani; Laila Qodariah; Mutiara Amanah; Syifa Husni Fadilah (SEAMEO CECCEP, 2023)
Learning and development are in their most rapid period during the first 5 years. Early identification and detection of developmental aspects in infant and young children is essential to maximize the child's potential, and to detect developmental delays early, so that appropriate interventions can be given. Developmental screening tools used in Indonesia today are still translations of screening tools in other countries and there has been no testing regarding their validity and reliability. Therefore, this study aims to develop an Early Child Development Questionnaire for 0-2 Years (ECD-Q) that is suitable for Indonesian children as a source of developmental screening tools. In this research, the process of developing this ECD-Q for 0-2 years old has used the design of measuring instrument development by Cohen & Swerdlik (2009), which consists of a test conceptualization, test construction, test tryout, analysis and revision. The analysis carried out in testing the ECD-Q is the value of internal consistency testing (Cronbach's Alpha), validity testing using CVI, and item analysis testing. Based on trials conducted on 280 mothers with children aged 0-24 months (Age of Mother: M=20.42; SD=4.3 and Age of Children: M=11.3 months; SD=6.8 months). This ECD-Q is a valid instrument based on content validity by expert review. Gross motor, cognitive, and self-help skills are reliable, and most of the items are also valid and have good discriminatory power. Developmental aspects of fine motor skills and language are reliable and can still be sensitive to distinguish the abilities of children over 13 months. In this final version of the ECD-Q, items that have an I-CVI score below 0.8 and have an item-total correlation of below 0.1 are deleted because they are considered less sensitive to distinguish children's abilities. Based on this ECD-Q trial, we recommend further research to increase the number of samples so that they can better represent the condition of children in Indonesia. The results of large-scale trials can be continued to establish group norms from this ECD-Q. A test-retest test would also be very good to see the consistency of this measuring instrument.